Avaliação do comportamento alimentar de Amblyomma sculptum Berlese, 1888 (AcariI: Ixodidae) em camundongos - Ana Carolina Marinho dos Santos (2018)
Amblyomma sculptum is an ixodid tick with wide distribution in the Americas, found from humid areas of northern Argentina, Bolivia, Paraguay to periamazonic areas in Brazil. A. sculptum is one of the six species belonging to the Amblyomma cajennense complex, with the broadest distribution among Brazilian states within the complex, being also important because it is the main vector of Brazilian Spotted Fever (BSF), which affects humans. Although there are studies related to the feeding behavior of ticks belonging to the Ixodidae family, and using the technique of electropenetrography, the number of studies about the subject is still reduced and, in the case of A. sculptum, until now, in the literature, there is no information about the feeding behavior using a similar technique. Thus, the present work aims to study in detail the feeding process of A. sculptum nymphs and females under laboratory conditions, when fed to mice at the different stages that occur throughout the entire food process of the arthropod. To this end, the electromyogram technique was used to capture the electrical signals produced by the tick during the feeding process.The analysis of the electrical activity profile of the pharyngeal pump allowed us to identify three events during haematophagy: suction, salivation and inactivity. These events were groupedduring the analysis and four groups of events were characterized for females: Suction-Salivation-Inactivity, Salivation-Inactivity, SuctionSalivation and Suction, whereas three were observed for nymphs: Suction-Salivation, Salivation-Inactivity, and Inactivity. In addition, we determined the predominant event per day of feeding and the suction frequency.These results provided new information about the A. sculptum feeding in a vertebrate host under laboratory conditions.